Analysis of Factors Affecting the Demand of Retail Sukuk - Muhammad Abdul Azis; Adventia Mega Wardhani; I Wayan Nudra Bajantika Pradivta; Sendey Prahasto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The development of the sharia financial industry in Indonesia can be seen from the increase in the number of Sharia Commercial Banks. The rapid development of the sharia financial industry is also followed by the rapid development of sharia financial instruments such as sukuk. Indonesia, through the ministry of finance, has issued 13 Retail State Sukuk types SR001 to SR013, starting in 2012, which has continued to increase in demand from year to year even though it had decreased in SR010 and SR012. Factors influencing the increase in the purchase of State Retail Sukuk are the minimum purchase, interest rates, and ORI coupons obtained by testing the data using statistical tests.